EVALUASI PENGELOLAAN KEUANGAN DAERAH KABUPATEN SORONG TAHUN 2010 - , Liza Renjaan ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study was carried out to evaluate the local financial management for expenditure using ASB model in Sorong Regency in office administration service program. The model meant here is to determine the total expenditure from fixed expenditure and variable expenditure, so that it was found out the applicable budget need appropriate with work load in that activity. Using ASB, the evaluation of financial management can be found out and the fairness value of expenditure can be calculated up to the expenditure object allocation in the program. Therefore, it can ease SKPD and TAPD in arranging the budget and to make ease the verification in program activity. The data used was secondary data coming from document of APBD realization in the budgeting year of 2009-2010 and DPPA SKPD year 2010. The analysis used was ASB and it was analyzed subsequently based on the arrangement of ASB made in Sorong Regency to see whether the expenditure budget in office administration service program in the year of 2010 experienced underfinancing or overfinancing. This study focused on Badan Perencanaan Pembangunan Daerah (Local Developmental Planning Official) of Sorong Regency. Based on the result of calculation, the fairness need of expenditure from total 12 programs, there was 11 programs experiencing underfinancing and 1 program experiencing overfinancing.